Navigating Colonial Power: Challenging Precedents and the Limitation of Local Elites - Siddiqui, Sohaira Z. M. (Islamic law and society, 2019)
Abstract In 1869, the British allowed Muslims to sit as judges on the High Court. This article explores the legal opinions of the first Muslim judge to be appointed to the High Court, Syed Mahmood. Straddling two competing worlds – that of Cambridge University and that of his native India – Justice Mahmood both legitimated and resisted colonial judicial power. In this essay I will demonstrate how British judges interpreted points of Islamic law within an English legal framework, and how these interpretations contradicted their translated texts of Islamic law, yet became the foundation of legal precedents established through the doctrine of stare decisis. Despite participating within the British colonial judiciary, Mahmood challenged these precedents, demonstrating his ability to navigate the paradoxes of colonial power to secure for himself a legitimate platform from which he could argue his juridical interventions. The efficacy of these challenges, however, ultimately was restrained by the institutions and structures of the colonial jural project.